Transcriptome signature in the blood of neuromyelitis optica spectrum disorder under steroid tapering - Yamamura, Ryohei; Kinoshita, Makoto; Yasumizu, Yoshiaki; Yata, Tomohiro; Kihara, Keigo; Motooka, Daisuke; Shiraishi, Naoyuki; Sugiyama, Yasuko; Beppu, Shohei; Murata, Hisashi; Koizumi, Naoshi; Sano, Itsuki; et al. (Frontiers in Immunology, 2025)
BackgroundThe advent of biologics has significantly transformed treatment strategies for neuromyelitis optica spectrum disorder (NMOSD). However, there are no biomarkers that predict relapses associated with steroid tapering; therefore, it is critical to identify potential indicators of disease activity. In this study, we collected peripheral blood mononuclear cells (PBMCs) from NMOSD patients during steroid tapering and performed bulk RNA sequencing to analyze changes in immune dynamics caused by steroid reduction.MethodsPBMCs were collected at 3–5 timepoints from 10 NMOSD patients at our hospital (including one relapse case), and bulk RNA sequencing was performed. All patients were positive for anti-AQP4 antibodies and had no history of biologic use.ResultsIn one relapsed patient, gene groups with decreased expression at relapse were observed predominantly in monocytes, with upregulation in anti-inflammatory pathways such as IL-10, while the upregulated genes were related to interferon signaling. Moreover, after steroid tapering, in non-relapsed patients, genes with increased expression were enriched in inflammatory pathways, represented by interferon signaling, while genes with decreased expression were enriched in pathways related to IL-10 and glucocorticoid receptors. Weighted gene co-expression network analysis identified modules that correlated with steroid dosage, and the modules inversely correlated with steroid dosage were enriched in monocytes, with marked immune signature of interferon pathway.ConclusionThis study identified peripheral blood transcriptome signatures that could lead to the identification of clinically relevant NMOSD disease activity biomarkers, and further highlights the pivotal role of interferon and IL-10 signaling in NMOSD.